A second crystalline modification of 2-{3-methyl-2-[(2Z)-pent-2-en-1-yl]cyclopent-2-en-1-ylidene}hydrazinecarbothioamide - Adriano Bof de Oliveira; Leandro Bresolin; Vanessa Carratu Gervini; Johannes Beck; Jörg Daniels (IUCrData, 2023)
A second crystalline modification of the title compound, C12H19N3S [common name: cis-jasmone thiosemicarbazone] was crystallized from tetrahydrofurane at room temperature. There is one crystallographic independent molecule in the asymmetric unit, showing disorder in the cis-jasmone chain [site-occupancy ratio = 0.590 (14):0.410 (14)]. The thiosemicarbazone entity is approximately planar, with the maximum deviation from the mean plane through the N/N/C/S/N atoms being 0.0463 (14) Å [r.m.s.d. = 0.0324 Å], while for the five-membered ring of the jasmone fragment, the maximum deviation from the mean plane through the carbon atoms amounts to 0.0465 (15) Å [r.m.s.d. = 0.0338 Å]. The molecule is not planar due to the dihedral angle between these two fragments, which is 8.93 (1)°, and due to the sp3-hybridized carbon atoms in the jasmone fragment chain. In the crystal, the molecules are connected by N—H...S and C—H...S interactions, with graph-set motifs R22(8) and R21(7), building mono-periodic hydrogen-bonded ribbons along [010]. A Hirshfeld surface analysis indicates that the major contributions for the crystal cohesion are H...H (67.8%), H...S/S...H (15.0%), H...C/C...H (8.5%) and H...N/N...H (5.6%) [only non-disordered atoms and those with the highest s.o.f. were considered]. This work reports the second crystalline modification of the cis-jasmone thiosemicarbazone structure, the first one being published recently [Orsoni et al. (2020). Int. J. Mol. Sci. 21, 8681–8697] with the crystals obtained in ethanol at 273 K.